Pengaruh Praktikum Shalat terhadap Pengamalan Ibadah Shalat Fardhu Mahasiswa Universitas Abdurrab - Muhammad Irham; Budi Satria; Azrha Azhiva; Zimanda Herko Netri (Prosiding Seminar Nasional Ilmu Pendidikan, 2024)
This research aimed to see whether there was an influence of the prayer practicum on the practice of Fardhu prayers for Abdurrab University students. The population in this research was all students from the 2022 class of Abdurrab University, totaling 600 people. The sample in this study was taken using a proportionate random sampling technique using the Slovin formula, namely 223 people. Data collection was carried out using a questionnaire technique, and the collected data was analyzed using regression analysis, namely Y = a + bX. The results of this research showed that the R2 (coefficient of determination) or R square value was 0.387, or 38.7%. This value could be interpreted as meaning that there was a change in the practice of students' fardhu prayers due to changes in the value of the independent variable practicum of worship by 38.7%, while 61.3% was determined by changes in other factors. The t-count value for the worship practicum variable is 3.234, with sig. 0.001 being smaller than 0.05, which means that there was an influence of prayer practicum on students' practice of Fardhu prayers. It can be concluded that Abdurrab University students' Fardhu prayer practices and their own prayer practices had an impact on one another.